Dielectric Properties of Vegetable Oils - Shah, Z. H.; Tahir, Q. A. (Journal of Scientific Research, 2011)
In search of PCB (polychlorinated biphenyl) free mineral oil used in transformer, we have carried out the detailed study on dielectric properties of some vegetable oils, such as corn oil and cottonseed oil. Dielectric constant, dielectric loss factor have been determined for corn oil, cotton seed oil, and PCB free mineral transformer oil having International Electrotechnical Commission number IEC-60296 in the frequency range 330 Hz to 3 MHz and in temperature range 250C to 700C. The dielectric data of the vegetable oils is critically compared with that of the transformer oil and appropriate causes for similarities and differences have been discussed. Owing to comparable results in the vegetable oils and transformer oil studied, it is suggested that vegetable oils may also be used as transformer oil. Keywords: dielectric constant; dielectric loss; dielectric relaxation; polarization. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:103329/jsr.v3i3.7049 J. Sci. Res. 3(3), 491-502 (2011)